2009
DOI: 10.1056/nejmoa0806218
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis in a Man with Complete Deletion ofUSP9Y

Abstract: Deletions in the azoospermia factor region AZFa on the human Y chromosome and, more specifically, in the region that encompasses the ubiquitin-specific peptidase 9, Y-linked gene USP9Y have been implicated in infertility associated with oligospermia and azoospermia. We have characterized in detail a deletion in AZFa that results in an absence of USP9Y in a normospermic man and his brother and father. The association of this large deletion with normal fertility shows that USP9Y, hitherto considered a candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 15 publications
2
81
0
5
Order By: Relevance
“…However, following findings revealed that what seemed to be a definitive result turned out to be just one of the possible phenotypes related to USP9Y deletion. In fact, Luddi et al (43) reported that this deletion has no effect on spermatogenesis and is thus compatible with fertility. On the other hand, previous studies (42,44,45) irrefutably demonstrate that the loss of the gene disturbs spermatogenesis to different degrees and that natural transmission is possible in case of a mild phenotype.…”
Section: Azf Gene-specific Deletionsmentioning
confidence: 99%
“…However, following findings revealed that what seemed to be a definitive result turned out to be just one of the possible phenotypes related to USP9Y deletion. In fact, Luddi et al (43) reported that this deletion has no effect on spermatogenesis and is thus compatible with fertility. On the other hand, previous studies (42,44,45) irrefutably demonstrate that the loss of the gene disturbs spermatogenesis to different degrees and that natural transmission is possible in case of a mild phenotype.…”
Section: Azf Gene-specific Deletionsmentioning
confidence: 99%
“…Actually, such a possibility is quite plausible because USP9X and USP9Y are almost identical proteins (61). However, considering that the complete deletion of the USP9Y-encoding gene in men has no deleterious effects (63), whereas deletion of USP9X in mice is embryonically lethal (64,65), and that USP9Y is probably expressed at much lower levels than USP9X, as assessed by the number of human/rat/mouse-expressed sequence tags presently available in the GenBank TM database (data not shown), the contribution of USP9Y for the hydrolysis of Ub-PEX5 in male animals, if any, is probably a minor one. For these reasons we focused our efforts in USP9X.…”
Section: Figure 1 Dub Acting On Ub-pex5 Is a Cytosolic Protein Amentioning
confidence: 99%
“…However, it was shown that USP9Y did not provide essential functions during spermatogenesis; mutations in USP9Y including deletion mutations were found to be transmittable in fertile patients (12)(13)(14). A second gene in the AZFa, DDX3Y, appears to represent the major spermatogenesis gene of this region (15,16).…”
Section: Discussionmentioning
confidence: 99%